Determinants of foreign direct investment in western Balkans - Arbër Krasniqi; Besnik Fetai (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2024)
Purpose: This study aims to establish the correlation between diverse economic and institutional factors and inward foreign direct investments (FDI) in Western Balkans countries. The analysis examines into the impact of market size, inflation rate, bank nonperforming loans, control of corruption, and rule of law on the relationship with inwards FDI. Design/methodology/approach: Ordinary least squares, fixed effects, random effects and Hausman Taylor IV models were applied to a balanced panel dataset comprising six western Balkans countries over the period 2008-2022. Our results provide evidence that past levels of FDI have a significant and positive impact on current FDI levels, even after accounting for endogeneity using instrumental variables. Findings: Our results provide evidence that past levels of FDI have a significant and positive impact on current FDI levels, even after accounting for endogeneity using instrumental variables. The coefficient for GDP per capita is negative, suggesting inverse correlation between GDP per capita and FDI. This relationship shows some marginal significance, indicating the possibility for further, more detailed studies to provide clearer insights in the future. Our findings suggest that inflation exhibits a positive and statistically significant relationship at the 0.01 level, implying that increased inflation rates correspond to higher levels of FDI. Over the course of our study period, the average inflation rate held at 3%. The results concerning the rule of law reveal a positive association with FDI. However, the coefficient for this variable is marginally significant (0.111), implying that stronger rule of law institutions may potentially attract higher levels of FDI. The results relating to control of corruption and bank nonperforming loans show no statistical significance. Research limitations/implications: While this study offers valuable insights into the factors influencing inward FDI in the Western Balkans, there are several limitations worth acknowledging. First, the analysis relies on a balanced panel dataset, which may not account for country-specific shocks or extreme events that could have affected FDI inflows during the study period. Another limitation is the reliance on certain macroeconomic and institutional indicators (GDP per capita, inflation, rule of law, corruption, and nonperforming loans), which may not encompass all the relevant factors influencing FDI. Future research could incorporate additional variables such as political stability, tax policies, or trade openness to provide a more comprehensive understanding of FDI drivers. Originality/value: This study offers a unique contribution to the literature on foreign direct investment (FDI) by specifically examining the relationship between FDI and a diverse set of economic and institutional factors within the context of the Western Balkans. While much of the existing research on FDI tends to focus on more developed economies or regions, this paper highlights the challenges and opportunities faced by transitional economies in Southeast Europe.
Keywords: F21; E22; 330; Foreign direct investment(FDI); GDP per capita; Inflation; Bank nonperforming loans; Control of corruption; Rule of law